Pemberian Kewenangan Hak Asuh Anak Kepada Ayah Prespektif Hukum Positif dan Hukum Islam - Nikmatul Kamila (Journal of Law and Islamic Law, 2023)
This study aimed to determine the judge's considerations in determining the decision number 1909/Pdt.G/2019/Pa.Bdw is based on positive law and Islamic law to determine the criteria behind transferring child custody to the father. To identify these problems, this study uses a normative qualitative research type with a statutory and case study approach. The data collection technique is to collect literature data according to the theme and then classify it into certain sub-chapters. This study concluded: The judge considered the decision Number 1909/Pdt.G/Pa.Bdw concerning granting custody of children to fathers based on positive law refers to article 105 KHI and article 49 paragraph (1) of the Marriage Law. Based on this article, the judges appointed the applicant as the child's biological father as the custody rights holder because the respondent (the biological mother) had neglected her duties as the hadhanah rights holder after a divorce. Meanwhile, based on Islamic law, the panel of judges based on the Book of Kifayatul Akhyar that a mother can lose her parental rights if the mother remarries. In positive law, no article states precisely the conditions for the holder of custody of their child. However, even so, the conditions that must be considered are the child's psychological condition, economic conditions, and hadhin holders must have good faith. In Islamic law, the requirements for a hadhin are contained in the Book of Kifayatul akhyar on page 587 that requirements to become a hadhin are intelligent, independent, Muslim, guarding honor, trustworthy, free from spouse and residence.